2013
DOI: 10.1038/nature11989
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated gene evolution through replication–transcription conflicts

Abstract: Summary Several mechanisms that increase the rate of mutagenesis across the entire genome have been identified; however, how the rate of evolution might be promoted in individual genes is unclear. A majority of the genes in bacteria are encoded on the leading strand of replication1–4. This presumably avoids the potentially detrimental head-on collisions that occur between the replication and transcription machineries when genes are encoded on the lagging strand1–4. We identified the ubiquitous (core) genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
188
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(197 citation statements)
references
References 30 publications
6
188
3
Order By: Relevance
“…We then determined the rate of accumulation of each type of SNP, in relation to protein length, for both strands. Our group, as well as others, has used gene length as a surrogate for conflict frequency (12,66), because replication and transcription machineries both spend an increased length of time traversing longer genes, increasing the chances for collisions. Because the analysis compares SNPs within species, the ancestral identity of a given nucleotide is unknown; thus, it is not possible to determine the directionality of the mutations.…”
Section: Poly1 Reduces Replication Stalling At Regions Of Lagging-strandmentioning
confidence: 99%
See 2 more Smart Citations
“…We then determined the rate of accumulation of each type of SNP, in relation to protein length, for both strands. Our group, as well as others, has used gene length as a surrogate for conflict frequency (12,66), because replication and transcription machineries both spend an increased length of time traversing longer genes, increasing the chances for collisions. Because the analysis compares SNPs within species, the ancestral identity of a given nucleotide is unknown; thus, it is not possible to determine the directionality of the mutations.…”
Section: Poly1 Reduces Replication Stalling At Regions Of Lagging-strandmentioning
confidence: 99%
“…This model was based on evolutionary analyses of several different B. subtilis genomes, where we found that highly conserved head-on genes accumulate amino acid-changing mutations at a higher rate compared with codirectional genes (12). Furthermore, based on experimental evidence, we proposed that the differential rate of mutagenesis for the genes in the two orientations is due to the two types of replication-transcription collisions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In nature, a wide continuum of phenotypes is observed in isolates from individual patients suffering from severe E. coli extraintestinal infections due to a tradeoff between self-preservation and nutritional competence as a consequence of variable levels of RpoS (22). Interestingly, the rpoS gene is located on the lagging strand, where the rate of point mutations is higher than on the leading strand, probably due to conflicts between replication and transcription (3). rpoS is also located close to the MR gene mutS, in a region that has high genomic variability as a result of horizontal gene transfer (23,24).…”
mentioning
confidence: 99%
“…Some regions of bacterial chromosomes are more prone to mutation (1)(2)(3)(4) or recombination (5) than other regions, due to physical or physiological constraints. Then, selection can favor diversification, for example, that of cell surface proteins such as beta barrel porins (6), and recombination events, which can restore particular functions, as in the case of the mismatch repair (MR) genes (7,8).…”
mentioning
confidence: 99%